Pengaruh Financial Self Efficacy dan Fintech Payment terhadap Manajemen Keuangan Pribadi Mahasiswa FEB Universitas Medan Area - Sitepu, Jefanya Franyuda; Siregar, M. Yamin; Wijaya, Muslim (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of Financial Self Efficacy and Fintech Payment on Personal Financial Management of Students of the Faculty of Economics and Business, Medan Area University. This research uses quantitative methods with causal associative research types. The sample of this study was 99 students of the Faculty of Economics and Business, Medan Area University using a sample collection technique, namely purposive sampling technique. Data collection was carried out by distributing questionnaires directly so that the collected data would be processed using SPSS to obtain research results. The results showed that partially Financial Self Efficacy has a positive and significant effect on Student Personal Financial Management, partially Fintech Payment simultaneously has a positive and significant effect on Student Personal Financial Management and simultaneously Financial Self Efficacy and Fintech Payment simultaneously have a positive and significant effect on Personal Financial Management of Students of the Faculty of Economics and Business, Medan Area University. Based on the results of the Coefficient of Determination (R2) test, it is found that the Adjusted R Square value is 0.745, describing that the value of variance owned by Personal Financial Management from the Financial Self Efficacy and Fintech Payment variables is 74.5% and the remaining 25.5% is influenced by other variables or faktors that are not examined and not explained.